A Strategic Implementation of the Average Tree Solution for Cycle-Free Graph Games - Rene van den Brink; Gerard van der Laan; Nigel Moes (Tinbergen Institute, 2012)
In this note we provide a strategic implementation of the average tree solution for zero-monotonic cycle-free graph games. That is, we propose a non-cooperative mechanism of which the unique subgame perfect equilibrium payoffs correspond to the average hierarchical outcome of the game. This mechanism takes into account that a player is only able to communicate with other players (i.e., to make proposals about a division of the surplus of cooperation) when they are connected in the graph.
urn:NBN:nl:ui:31-1871/38472
Keywords: C71; C72; 330; implementation; cycle-free graph game; tree game; hierarchical outcome; average tree solution; weighted hierarchical outcome; Kooperatives Spiel; Nichtkooperatives Spiel; Graphentheorie